Dietary effects on breast cancer molecular subtypes, a 1:2 paired case–control study. Issue 10 (31st August 2020) - Yuan, Guohai; Zhang, Jingjing; Ren, Yi; Ding, Wei; Du, Yan; Zhang, Lu; Shao, Jihong
Abstract: To explore the associations between dietary factors and breast cancer (BC) molecular subtypes. The retrospective cases were confirmed by pathological diagnosis with breast cancer were gathered in two major hospitals in Xuzhou city, China, from 2015 to 2016. These cases were classified by the meeting standard of 13th St Gallen: luminal A, luminal B, Her‐2 overexpression, and triple‐negative breast cancer (TNBC) subtypes. A 1:2 paired retrospective case–control study with 210 cases and 420 controls was conducted to evaluate individual dietary intake, by food frequency questionnaire (FFQ) and estimate odds ratios ( OR s), by the Cox regression model. For overall breast cancer patients, the more frequency of red meat ( OR  = 1.002, 95% CI  = 1.001–1.004) and salted food ( OR  = 1.003, 95% CI  = 1.001–1.005) were statistically significantly associated with a greater risk of breast cancer. Beans ( OR  = 0.997, 95% CI  = 0.995–0.999), white meat ( OR  = 0.993, 95% CI  = 0.989–0.997), aquatic products ( OR  = 0.990, 95% CI  = 0.984–0.996), vegetables ( OR  = 0.999, 95% CI  = 0.999–0.999), fruit ( OR  = 0.998, 95% CI  = 0.997–0.999), and green tea ( OR  = 0.997, 95% CI  = 0.994–0.999) were significantly associated with a lower risk of breast cancer. For luminal breast cancer patients, beans ( OR  = 0.997, 95% CI  = 0.994–0.999), white meat ( OR  = 0.992, 95% CI  = 0.987–0.997), green tea ( OR  = 0.995, 95% CI  = 0.991–0.999), and milk ( OR  = 0.998, 95% CI  = 0.996–0.999) were protective factors. While for nonluminal breast cancer, red meat was not included in the equation, and beans ( OR  = 0.989, 95% CI  = 0.981–0.997), white meat ( OR  = 0.989, 95% CI  = 0.981–0.998), vegetables ( OR  = 0.998, 95% CI  = 0.997–0.999), and milk ( OR  = 0.994, 95% CI  = 0.989–0.999) still showed a significantly reduced risk of nonluminal breast cancer. Different dietary factors revealed different effects on the etiology of breast cancer. Red meat may be a specific risk factor for luminal‐type breast cancer. Abstract : The paper was to explore the associations between dietary factors and breast cancer molecular subtypes by food frequency questionnaire. The result showed that different dietary factors revealed different effects on the etiology of breast cancer, and red meat may be a specific risk factor for luminal‐type breast cancer.